Kesiapan Mahasiswa Menghadapi Pembelajaran Daring di Masa Pandemi Covid - 19 - Ni Luh Putu Nina Sriwarthini; Muhammad Syazali; Deni Sutisna (Prodi Sosiologi Universitas Mataram, 2020)
The education sector is one of the many sectors that most feel the impact of changes due to the covid-19 pandemic. Starting from early childhood education level to higher education level has now started to try to adapt to the covid-19 pandemic situation. The purpose of this research is to get information on student readiness, especially PGSD study program in facing online learning during the covid-19 pandemic. Student readiness is reviewed from 3 aspects, namely, readiness in terms of facilities and infrastructure owned, readiness in terms of the ability to use media / online learning platforms, and readiness in facing obstacles that will arise when online learning is implemented. The subjects of this study were students of PGSD FKIP Mataram University semesters 1, 3, and 5. This research is a qualitative descriptive research. Data collection is done by disseminating questionnaires and interviews to students in each semester. The data obtained is then analyzed using miles and huberman analysis model (Analysis Interactive Model). The results of the research showed that most PGSD students are ready to carry out online learning during the covid-19 pandemic, reviewed in terms of readiness in terms of facilities and infrastructure owned, readiness in terms of the ability to use online media / learning platforms, and readiness in facing obstacles that will arise when online learning is implemented.